1973
DOI: 10.1136/hrt.35.12.1280
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a pacemaker clinic to prevent sudden pacing failures.

Abstract: Two hundredpatients with implantedpacemakers werefollowed in a pacemaker clinic over a period of 3years. The follow-up times ranged from I to 36 months, with a mean of 22 months. The material represents 366 patient-years ofpacing and 361 pacemakers. One hundred and twenty replacements were done. Most of these were elective (93%) and based on gradual deterioration of the pacing detected by photoanalysis of the generator impulse. Of the single variables the duration of the impulse and the discharge rate were mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1975
1975
1978
1978

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It must also be emphasized that in none of the pulse generators had the voltage fallen below 3.5 volts implying that stimulation was uninterrupted in all. The frequency of battery exhaustion found over a period of two years does not appear to exceed that in other miterials (Frick 1973 andGreen 1974). However, it is difficult to compare pacemakers of different makes if they have not been implanted at the same clinic with the same criteria for replacement, Green (1974) has shown that a steady improvement has taken place in the pulse generators he has used during the 71/* year period in which he has studied them systematically.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It must also be emphasized that in none of the pulse generators had the voltage fallen below 3.5 volts implying that stimulation was uninterrupted in all. The frequency of battery exhaustion found over a period of two years does not appear to exceed that in other miterials (Frick 1973 andGreen 1974). However, it is difficult to compare pacemakers of different makes if they have not been implanted at the same clinic with the same criteria for replacement, Green (1974) has shown that a steady improvement has taken place in the pulse generators he has used during the 71/* year period in which he has studied them systematically.…”
Section: Discussionmentioning
confidence: 92%
“…The method has shown great xnsitivity primarily for revealing reduction in the power of the pacemaker battejiey. Its clinical value is well documented (Escher et al 1970, Parsonnet et al 1970, Edhag et al 1971, Smith et al 1971, Frick 1973, Zion et al 1973and Green et al 1974).…”
mentioning
confidence: 99%
“…Measurements are available for 13 pacers, and in Pig. 2 the output actually measured is related to the output calculated from skin potential measurements.…”
Section: Gain In Lifetime Of Pulse Generatorsmentioning
confidence: 99%
“…The number of patients on permanen't cardiac pacing is rapidly increasing. Pacemaker clinics are established in many hospitals (1,2,3 ) , and an increasing number of hours is spent by doctors, nurses and technicians in the clinical control of these patients. In this brief analysis we will try to evaluate the effect of our pacemaker clinic, with regard to patients safety and increased lifetime of pulse generators.…”
mentioning
confidence: 99%